ANALYSIS OF WATER PERFORMANCE AT GRAHA JANGLI INDAH SEMARANG - Suharyanto Suharyanto; Budiono Joko Nugroho; Sri Sangkawati (Fakultas Teknik Universitas Muhammadiyah Sumatera Barat, 2021)
The clean water network system is made to meet the needs of clean water in a city or community and for Graha Jangli Indah, clean water management is carried out by the Graha Jangli Indah Water Management. The purpose of this study is to find out the performance of clean water network services managed by the Water Management Board of Jangli Indah by analyzing the network service performance of the network's ability to meet the minimum needs of customers in terms of water discharge. In addition, an analysis of customer satisfaction was carried out on the Water Management of Graha Jangli Indah. the level of clean water service network at Graha Jangli Indah is still unsatisfactory, with a reliability of only around 49.33%, with the length of time the system will be in a state of failure of about 5.83 months, and with a very average percentage deficit discharge rate which varies between 1.12% to 102.11%. So that the system's resilience index or ability to return to normal conditions is 0.17 (1.03 times failure divided by 5.83 months). This is because the average discharge at Graha Jangli Indah has an average water discharge value of 17.8 m3 per month which is still below the standard water demand based on Domestic Water Needs for the Big Cities category of 20.4 m3. For the calculation of the value of have rated the performance of Graha Jangli Indah Management services with very good value. With 7 indicators entering quadrant II so that conclusions can be drawn by the Importance and Performance Analysis (IPA) method, the performance of the Graha Jangli Indah Water Management is quite satisfying.